Interrelation between the Choice of Investment Trend and Subsequent Economic Results and Strategy of Sustainable Development in Organization - E. U. Ganshina; I. L. Smirnova; S P. Ivanova (Вестник Российского экономического университета имени Г. В. Плеханова)
The topic of making investment and choosing the most effective trends of investing money is becoming more acute for today’s organizations due to numerous crisis economic events and accompanying difficulties with capital reproduction. In researching options of investment special attention is paid to strategic aspects of alternative financial and technological opportunities of putting in resources and forecasting the horizon of recovery of the investment. Apart from this, the research interest is aroused by the impact of basic lines of enterprises’ investment on the level of their economic results together with trends of providing long-term sustainable development. The authors analyzed cases of the biggest Russian industrial organizations, identified correlation between investment flows within the frames of the organization and the effect of investment on the basis of consolidated accounting of these companies. The article analyzes some investment projects of the NMLK Group and the PAO Sibur, for instance, introduction of innovation model of making forecast concerning breaking-down of critical equipment and the system of corporate social responsibility. The authors made recommendations on prioritization of aspects of socially important trends of investment for today’s big companies, which could lead to raising efficiency of organizations’ work and thus to principles of sustainable development